PERANAN KEPALA DESA DALAM PEMBANGUNAN DI DESA TIMPUK KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Adrianus Numan E42009066 (FISIP Universitas Tanjungpura Pontianak, 2013)
AbstracThis study aimed to determine the role of village heads in the planning, implementation andmaintenance of development outcomes and the factors that cause has not been strong involvement inthe development of the village chief in the Village District Timpuk Sekadau Sekadau Hilir district.Title of thesis concerns raised by the village chief role is not optimal in development.This study usesa qualitative descriptive approach. Data collection technique is participant observation, in-depthinterviews, and documentation. Activity analysis includes data reduction, data display, andconclusion. Research sites in the Village District Timpuk Sekadau, Sekadau Hilir district. Theresearch subject is the village head, village government officials and village residentsTimpuk.Results of this study indicate that it is still not optimal role in the development of the villagehead is seen from the lack of ability to move the village head Keywords: Roles, head of the village, development, communication, participation